WHEN IN STELLIS: AN AUTO-ARCHAEOLOGY OF A DIGITAL ARTIFACT COLLECTION FROM TEARS OF THEMIS - Guzman, Kevin Michael De (International Journal of Humanity Studies (IJHS), 2024)
Primarily, this research aimed to appraise and discover how a 21st-century Filipino object owner collocates meaning with digital artifacts and identify what cultural underpinnings influence the affinity with these things. Two novel ideas in contemporary archaeology were utilized in this study: (1) auto-archaeology, a method of employing archaeological analysis on one's objects, and; (2) archaeogaming, which treats digitally constructed objects as artifacts (Reindhard, 2018). Using these postmodern perspectives, I conducted an auto-archaeology of my collection of digital artifacts from the game Tears of Themis (COGNOSPHERE, 2020) and aimed to unearth a retelling of my recent past as a posthuman Filipino. Informed largely by Ellersdorfer's (2021) autoethnographic archaeology and Woods' (2022) gacha game discourse, my case study involved extracting memories from select pieces from my collection of digital artifacts. Findings reveal that not only can these objects reconstruct their distinct semiotic context through the game design, story of acquisition, and in-game usage but also deconstruct off-game contexts that are personally attached by an individual owner to its immateriality through perception and affective embedding. In so doing, the digital artifacts amplify the different voices inscribed within each artifact in its decontextualized form as a unit in a rhizomatic network of digital objects.